CMOS impulse radio ultra‐wideband Gaussian pulse generator with variable channel and bandwidth. Issue 2 (1st March 2016) - Choi, Jamin; Kwon, Ickjin
Abstract : A Gaussian pulse generator for an ultra‐wideband impulse radio transmitter is presented. The proposed generator is based on digital intensive circuits, and the centre frequency and bandwidth of a pulse are controlled by a digitally tunable delay circuit and pulse‐width control circuit. The Gaussian pulse is obtained by a weighted summing amplifier that is controlled by a digital switching signal without an additional LC filter. The amplifier uses a Gaussian pulse shaper that has tunable weighting factors with bandwidth control. The energy consumption of the pulse generator is 37.4 pJ/pulse, and sidelobe rejection of 20 dB is achieved without a filter.